Low-fat and fat-free spindle cell lipomas in the oral cavity: Immunohistochemical analysis and review of the literature - Rocha, Audrey F. L. [UNESP]; Miotto, Larissa N. [UNESP]; Ferrisse, Túlio M. [UNESP]; Silveira, Heitor A. [UNESP]; Almeida, Luciana Y.; Bufalino, Andreia [UNESP]; Navarro, Cláudia M. [UNESP]; León, Jorge E. (Wiley, 2019)
The low-fat and fat-free spindle cell lipomas (SCLs) are rare and often mistaken for other benign and malignant morphological mimics, because of the fact that the diagnosis relies on its non-lipogenic component analysis. Here, we report the clinicopathological features of two oral SCLs (low-fat and fat-free variants). Both lesions presented clinically as an asymptomatic nodule, which initially yielded diagnostic difficulties on the morphological analysis alone. One case was diagnosed as low-fat SCL on the lower lip in a 29-year-old man, and the other as fat-free SCL on the buccal mucosa in a 46-year-old man. In both cases, immunohistochemistry showed strong positivity for CD34 and, remarkably, retinoblastoma (Rb) protein was deficient. Mast cell (MC) tryptase and toluidine blue stain highlighted numerous MCs distributed throughout all tumor stroma. Alpha-SMA and desmin were negative. S100 evidenced scarce adipocytes only in the low-fat SCL case. Conservative surgical treatment was performed and no recurrence was noticed in about 2-year of follow-up in both cases. Because of the potential pitfalls, careful morphological analysis of the tumor stroma in the low-fat/fat-free SCL diagnosis, supported by immunohistochemistry (especially CD34, Rb and MC tryptase), is strongly recommended. To the best of our knowledge, these are the first and second cases reported of fat-free and low-fat SCL in the oral cavity.
Keywords: histopathology; immunohistochemistry; low-fat/fat-free lipoma; oral cavity; spindle cell lipoma